Characterization of oxidative stress in animal model of neonatal hypoxia - Bochenek,Liliane de Mello Santos (2021)
ABSTRACT Purpose To evaluate the oxidative stress in swine neonates submitted to hypoxia. Methods Ten large white piglets, healthy newborns, of both sexes, were divided into two groups and submitted to an experimental hypoxia protocol with reduced inspired oxygen fraction. The hypoxia group, composed of six animals, was submitted to oxygen reduction for 180 min. The animals in the control group, n = 4, were handled and evaluated simultaneously, but without oxygen reduction. Results 180 min after the start of the hypoxic insult, a significant difference was observed in the oximetry, and heart rate of the hypoxia group was compared to the control group (p<0.05). There was no significant difference in the oxidative stress analyses. Reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), lipid peroxidation (TBARS), protein carbonyl (PC), and myeloperoxidase (MPO) in the piglets’ brain tissue were analyzed. Conclusions Hypoxia causes adverse effects in swine neonates, although there is a natural physiological resistance of swine neonates to respond to this insult. Analyses of GSH, SOD, CAT, TBARS, MPO, and PC were tabulated and are presented as parameters for further studies to be carried out on an animal model of swine hypoxia.